Clinical implications of the histologically and immunohistochemically detected solitary lymph node metastases in gastric cancer. - Griniatsos, J; Yiannakopoulou, E; Gakiopoulou, H; Alexandrou, A; Dimitriou, N; Karavokyros, I; Felekouras, E (Scand J Surg, 2011)
BACKGROUND: Topographic correlation between the primary gastric tumor and the first peri- and extragastric lymphatic drain basin (solitary lymph node metastasis) on gastrectomy specimens, represents a reliable method to investigate and understand the exact pattern of lymphatic drainage from a gastric tumor. Analyzing that correlation, useful information regarding the extent of the appropriate oncological perigastric lymphadenectomy will be provided. We retrospectively evaluate the usefulness of a modified D2 lymphadenectomy in gastric cancer patients, based on the topographic correlation between the primary tumor and the location of the solitary lymph node metastases, as they were detected by histology and immunohistochemistry. MATERIALS AND METHOD: Between April 2003 and March 2010, 134 gastric cancer patients were submitted to a modified D2 lymphadenectomy. Postoperatively, the standard histological ex-amination by hematoxylin and eosin (HE) staining, disclosed metastatic infiltration of at least two lymph nodes in 90 patients, solitary lymph node metastases were histologically detected in 10 patients, while the remaining 34 patients were classified as pN0. All lymph nodes of the ten patients with histological solitary lymph node metastases, as well as the 34 patients who had been classified as pN0 by histology, were further submitted to immunohistochemistry for micrometastases detection. More than one micrometastases were detected in none of them, while in seven patients solitary micrometastases were detected either in the level I perigastric or in the level II extragastric lymph nodes stations (skip micrometastases). RESULTS: Solitary lymph node metastases were detected by histology in ten patients and by immunohistochemistry in additional seven (nine females and eight males). Solitary metastases were detected in the level I LN stations in seven patients (four by histology and three by immunohistochemistry) and in the level II LN stations in ten patients (six by histology and four by immunohistochemistry). In order of frequency, the solitary lymph node metastases were located in the no 7 (n = 6), no 6 (n = 4), no 9 (n = 2), no 5 (n = 2), no 4 (n = 1), no 8 (n = 1) and no 12 (n = 1) LN stations. Skip metastases encountered the 60% of the histologically detected, 57% of the immunohistochemically detected and 59% of all solitary lymph node metastases. 80% of solitary metastases in the level II LN stations, were mainly located in the nos 7-9 lymph node stations complex. Tumors of the lower and middle-third of the stomach were equally drained both to the level I and level II lymph node stations, while 67% of the tumors towards the lesser curvature, were mainly drained in the level II lymph node stations. CONCLUSION: D2 lymphadenectomy increases the number of true R0 resections. Thus, a modified D2 lymphadenectomy should be routinely performed in gastric cancer patients.
Keywords: Adenocarcinoma; Aged; Aged, 80 and over; Female; Gastrectomy; Humans; Immunohistochemistry; Lymph Node Excision; Lymphatic Metastasis; Male; Middle Aged; Retrospective Studies; Stomach Neoplasms